PWE-081 Low serum transferrin indicates short-term mortality in severe alcoholic hepatitis. (17th June 2017) - Atkinson, S; Spivak, I; Cabezas, J; Bataller, R; Trautwein, C; Thursz, M; Strnad, P
Abstract : Introduction: Iron is simultaneously an essential and potentially toxic micronutrient linked to oxidative stress, bacterial infection and systemic inflammation. The liver plays a key role in iron homeostasis through synthesis of the serum transporter, transferrin, and the iron hormone hepcidin. Dysregulation of iron parameters is common in patients with severe alcoholic hepatitis and serum transferrin has been associated with outcome in patients with decompensated alcohol-related liver disease. The aim of this study was to examine the relationship between parameters of iron metabolism and outcome in patients with severe alcoholic hepatitis. Method: Ferritin, transferrin, iron, transferrin saturation (TSAT) and hepcidin were measured in baseline, pre-treatment, serum samples from 202 randomly selected patients with severe alcoholic hepatitis (AH) recruited prospectively via the STOPAH trial. Hepatic transferrin mRNA expression was assessed in 27 additional AH subjects. Results: Compared to population-based normal ranges AH patients had diminished serum transferrin (median 93 mg/dl), but increased ferritin (median 625 ng/dl) and TSAT (median 69.8%). Transferrin was negatively correlated with MELD (r=-0, 26; p<0.001) and the Glasgow Alcoholic Hepatitis score (GASH; r=−0.31; p<0.0001). Low transferrin and raised hepcidin, ferritin and TSAT were associated with 28 day mortality. Serum transferrin remained an independent predictor of 28 day mortality on multivariable analysis (OR 0.98, 95% CI 0.97–0.99, p=0.005). The ability of transferrin to predict 28 day survival (AUROC 0.70, 95% CI 0.61–078) was greater than MELD, GAHS or discriminant function (AUROCs 0.66, 0.69 and 0.59, respectively). Analysis of hepatic mRNA levels demonstrated negative correlation between transferrin and IL8, CXCL5, Fn14 and DR6. Moreover, a marked negative correlation between transferrin mRNA levels and the hepatic venous pressure gradient was observed (r=−0.54, p=0.004). Conclusion: Our findings demonstrate that parameters of iron metabolism, particularly transferrin as a negative acute phase reactant, are strongly associated with outcome in severe AH. Moreover, the performance of transferrin in predicting 28 day mortality is comparable to the commonly used scoring systems. Further studies are needed to determine factors influencing transferrin availability in AH. Disclosure of Interest: None Declared